2020
DOI: 10.1016/j.ejrad.2020.109336
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary thromboembolic disease in COVID-19 patients on CT pulmonary angiography – Prevalence, pattern of disease and relationship to D-dimer

Abstract: Highlights Prevalence of pulmonary thromboembolic disease (PTE) is 38% in COVID-19 patients who underwent CTPA. Patients with more severe COVID-19 changes are more likely to have PTE. Majority of PTE is observed within smaller pulmonary vessels (75%) and lungs demonstrating COVID-19 changes (72%). Subsegmental vessels should be scrutinized for presence of PTE. D-dimer values may have potential in guiding anticoagulation therapy and evaluating prognosis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
62
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 24 publications
10
62
0
2
Order By: Relevance
“… 28 , 29 Imaging studies have confirmed that the radiological appearance of PE differs in COVID-19 compared with non–COVID-19 patients, with more peripheral localization of thrombi and generally lower clot burden. 30 , 31 These observations may support the hypothesis that for patients with COVID-19, PE may result from in situ immunothrombosis rather than from embolization from lower-extremity DVT. In this report, the term PE is used to collectively refer to both embolus and in situ thrombus of the pulmonary arteries.…”
Section: Introductionsupporting
confidence: 56%
“… 28 , 29 Imaging studies have confirmed that the radiological appearance of PE differs in COVID-19 compared with non–COVID-19 patients, with more peripheral localization of thrombi and generally lower clot burden. 30 , 31 These observations may support the hypothesis that for patients with COVID-19, PE may result from in situ immunothrombosis rather than from embolization from lower-extremity DVT. In this report, the term PE is used to collectively refer to both embolus and in situ thrombus of the pulmonary arteries.…”
Section: Introductionsupporting
confidence: 56%
“…The reported frequency of pulmonary embolism in critically ill COVID-19 patients is approximately 20%-30%[ 6 , 7 ]. Evidence suggests that small vessel pulmonary thrombi are more common than large pulmonary vessel involve-ment in COVID-19[ 8 , 9 ]. Pulmonary embolism is a serious thrombotic complication of COVID-19 pneumonia, with mortality rates for patients with COVID-19 and PE estimated at approximately 45%[ 10 ].…”
Section: What Is the Risk Of Vte In Covid-19?mentioning
confidence: 99%
“…[44,45] Both fibrinogen levels and D-dimer levels have been shown to be elevated in COVID-19 patients, especially in severe cases who develop thromboembolic complications, and who only respond to higher doses of antithrombotic treatment. [9,2123,28,29,46,47] Additionally, heparin resistance has been reported in COVID-19 patients. [48,49] and could therefore explain the failure of anti-thrombotic therapies in some patients in reducing coagulopathy.…”
Section: Discussionmentioning
confidence: 99%